Risk Assessment in Financial Feasibility of Tanker Project Using Monte Carlo Simulation - Muhammad Badrus Zaman; Dwi Priyanta; Filik Trisilo (International Journal of Marine Engineering Innovation and Research, 2017)
Every ship project would not be apart from risk and uncertainty issues. The inappropriate risk assessment process would have long-term impact, such as financial loss. Thus, risk and uncertainties analysis would be a very important process in financial feasibility determination of the project. This study analyzes the financial feasibility of 17,500 LTDW tanker project. Risk and uncertainty are two differentiated terminologies in this study, where risk focuses on operational risk due to shipbuilding process nonconformity to shipowner finance, while uncertainty focuses on variable costs that affect project cash flows. There are three funding scenarios in this study, where the percentage of funding with own capital and bank loan in scenario 1 is 100% : 0%, scenario 2 is 75% : 25%, and scenario 3 is 50% : 50%. Monte Carlo simulation method was applied to simulate the acceptance criteria, such as net present value (NPV), internal rate of return (IRR), payback period (PP), and profitability index (PI). The results of simulation show that 17,500 LTDW tanker project funding by scenario 1, 2 and 3 are feasible to run, where probability of each acceptance criteria was greater than 50%. Charter rate being the most sensitive uncertainty over project's financial feasibility parameters.